1988
DOI: 10.1111/j.1439-0450.1988.tb00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Estudio serológico de Leucosis Enzoótica Bovina en un predio de la provincia de Valdivia y su relación a parámetros productivos y reproductivos

Abstract: Summary Enzootic Bovine Leukosis. Serological study in a farm of the province of Valdivia and relation with productive and reproductive parameters Enzootic Bovine Leukosis is a cattle disease which has been known for many years in Chile. Nevertheless, there are no systematic studies regarding how the disease fluctuates with age and time. With the purpose of finding out the economic importance of the disease, its age group distribution and its probable influence on reproductive and productive parameters, the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…• Reinhardt et al (1988) state that bovine leucosis has no influence on abortion, mastitis or fertility. However, they found that positive animals had an average milk loss of 156 kg, which in a herd of 137 cows with 30% prevalence was equivalent to US$74,880/year.…”
Section: Bovine Leucosismentioning
confidence: 99%
“…• Reinhardt et al (1988) state that bovine leucosis has no influence on abortion, mastitis or fertility. However, they found that positive animals had an average milk loss of 156 kg, which in a herd of 137 cows with 30% prevalence was equivalent to US$74,880/year.…”
Section: Bovine Leucosismentioning
confidence: 99%
“…Las pérdidas económicas son debidas a muertes prematuras, reemplazo de animales enfermos y disminución de la producción láctea, así como por las restricciones de importación y exportación impuestas por algunos países (Benavides et al, 2013). No obstante, en un hato lechero en Chile con 30% de seroprevalencia no se encontraron efectos negativos sobre fertilidad, aborto o mastitis, pero se observó una pérdida promedio de 156 kg de leche por campaña por animal (Reinhardt et al, 1988). Por otro lado, en fincas lecheras de Canadá con seroprevalencias de 29% no se encontraron efectos adversos sobre la producción de leche, grasa o proteína (Tiwari et al, 2007); sin embargo, se estima que los costos por tratamientos y las pérdidas económicas equivalen a US$ 800 al año para un hato de 50 vacas y con una prevalencia del 19% (Chi et al, 2002).…”
Section: Introductionunclassified